The Influence of Carrie TV Channel Shows on Language Acquisition in Early Childhood - Tri Wahyono; Riana Mashar (LPPM State University of Jakarta (Program Studi Pendidikan Bahasa dan Sastra Indonesia dan LPPM Universitas Negeri Jakarta), 2020)
The role of technology media as a stimulant in the industrial era 4.0 has developed rapidly and varied to affect various aspects of life in all circles, including early childhood. One affected aspect of life is language. The influence on the linguistic aspect is felt by children, especially at an early age. This study aims to determine how the influence of digital media broadcasts on Carrie TV’s YouTube channel on language development and acquisition in early childhood. This research utilized the observation method by observing language attitudes in early childhood and recording speech in communication activities. The observation technique was carried out by recording the distribution of words uttered by early childhood. Moreover, a comparison of the spoken vocabulary was made between the children who watched the Carrie TV channel and those who did not watch it. The word distribution recorded was adjusted to the children’s vocabulary skills in general based on their language development stage. The results revealed that childhood who watched the Carrie TV channel possessed more vocabulary than those who did not watch it. The children’s vocabulary could be categorized into basic words, conjunctions, affix words, and word combinations.